Guidance for the Rabbani Generation: Preparing Oneself for the Best Destiny at Ponpes Tahfidzul Qur’an Ainun Darusshofa Awang Noor, Baran, Meral District, Karimun Regency, Riau Islands - Sandika Saputra; Mohamad Mahrusillah (IRDH International Journal of Social Sciences & Humanities, 2025)
This research is specifically aimed at students averaging 13 years old and under who are in a crucial phase of character development. The background of this seminar is the urgent need to instill Islamic values comprehensively, not only in cognitive aspects in the form of memorizing the Qur'an but also in the affective and psychomotor dimensions, including noble character, love for knowledge, and deep spiritual awareness. The main purpose of the activity is to shape a rabbani generation that possesses a balance between mastery of knowledge, earnestness in worship, and moral responsibility in everyday life. Through this seminar, the students are guided to understand the importance of setting intentions in seeking knowledge, maintaining decorum towards teachers and peers, and fostering a life vision aimed at earning the pleasure of Allah SWT. The delivery method is carried out in an educational, motivational, and interactive manner through lectures, question and answer sessions, and practical illustrations relevant to the children's lives. Thus, the material can be easily received, enjoyable, and memorable for the participants. The results of the seminar show an increase in the understanding of the students regarding the concept of a righteous generation, reflected in their enthusiasm in discussions and their ability to explain the materials presented. Additionally, there has also been a growing motivation to be more serious in memorizing the Qur'an, improving their moral character, and preparing themselves for a better future. With continuous guidance, it is hoped that the students can become individuals who are steadfast, knowledgeable, possess good character, and are ready to face the challenges of the times based on faith and good deeds